2021
DOI: 10.1002/ana.26266
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Surgical Extent for Memory and Seizure Outcome in Temporal Lobe Epilepsy

Abstract: Objective: Postoperative memory decline is an important consequence of anterior temporal lobe resection (ATLR) for temporal lobe epilepsy (TLE), and the extent of resection may be a modifiable factor. This study aimed to define optimal resection margins for cognitive outcome while maintaining a high rate of postoperative seizure freedom. Methods: This cohort study evaluated the resection extent on postoperative structural MRI using automated voxelbased methods and manual measurements in 142 consecutive patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 47 publications
(108 reference statements)
2
22
0
Order By: Relevance
“…However, TLE research suggests involvement in semantic processing. Research using voxel‐lesion symptom mapping found that resection of a small area of the STG correlated with naming decline following ATLR 56 . DES research did not find significant differences in naming sites in the STG between those with lesional and nonlesional TLE 51 .…”
Section: Functional Anatomy Of Language: Cortical Areasmentioning
confidence: 88%
“…However, TLE research suggests involvement in semantic processing. Research using voxel‐lesion symptom mapping found that resection of a small area of the STG correlated with naming decline following ATLR 56 . DES research did not find significant differences in naming sites in the STG between those with lesional and nonlesional TLE 51 .…”
Section: Functional Anatomy Of Language: Cortical Areasmentioning
confidence: 88%
“…39,40 The BIRT memory battery has also been validated against the histological severity of hippocampal sclerosis in temporal lobe epilepsy and is sensitive to decline following anterior temporal lobe resection. 41,42 While the WASI and BIRT are not commonly used in MS research, previous work has found that lower WASI Full Scale IQ was associated with slower walking speed and higher risk of falls in a cohort of 78 pwMS and baseline WASI performance has been reported in a randomised controlled trial of cognitive rehabilitation for pwMS. 43,44 In summary, we felt that the requirement for more comprehensive cognitive outcome measures was warranted given the aim and hypotheses of the original MS-STAT interventional trial.…”
Section: Discussionmentioning
confidence: 99%
“…Lesional mesial temporal lobe epilepsy usually include hippocampal sclerosis, focal cortical dysplasia, or local neurodevelopmental tumors [53,54]. Due to their limited focal damages, standard anterior temporal lobectomy offers comparatively favorable outcomes (50-80% seizure-free rate) [55,56]. However, if combined with an extended frontal or thalamic 18 F-FDG metabolic disturbance, actual lesions associated with epileptogenesis or seizure related networks in MTLE may be larger than they appear on structural imaging.…”
Section: Discussionmentioning
confidence: 99%